MOTIVASI INDONESIA MENERAPKAN REGULASI SNI TERHADAP MAINAN IMPOR STUDI KASUS: PRODUK MAINAN IMPOR DARI CINA - Yuliandita, Alpina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research would explain about Indonesia Motivate to apply SNI Regulation for import‘s toys. This study used a qualitative descriptive method. The ASEAN-China Free Trade Area (ACFTA) agreement is Indonesia's economy has improved or deteriorated. This study used a qualitative descriptive method. The results of this study is the ACFTA a positive impact on SMEs in Indonesia, because ACFTA growing number of SMEs in Indonesia.A toy is an object which has close relationship whit child safety. As its primary consumer.Many accidents were happen to the children due to misused, not applyto the age concern. Since toys may create accident for the children, several countries has obliged their standards as a technical requirement for the product to comply if they want to be marketed in the country. Indonesia plans to implement the toys standards. The readiness of SNI was conducte throught analyzing the availibility of SNI compare to international reference. Standardization is one of the instruments of technical regulations that can protect the interests of consumers nationwide and as well as domestic producers. Through technical regulations based on standardization can be prevented circulation of goods that are not qualified in the domestic market, especially related to health, safety, security, and environment conservation. Through the same instrument, can be prevented the entry of imported goods of low quality which distort the domestic market because of low-priced.The research shows that Indonesia took strategy to apply SNI of import’s toy with preasure the import’ toys use in regulation to be increas national product competition.Keywords:Motivation,toys,ACFTA, Import, technical regulations, mandatory SNI.